BIAS GENDER PADA TOKOH PEREMPUAN DALAM NOVEL ZI<NAH KARYA NAWA<L AS-SAâDA<WI<: ANALISIS KRITIK SASTRA FEMINIS - , MUASOMAH; , Zulfa Purnamawati, S.S., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Zi>nah is a novel written by a famous writer of Egypt, Nawa>l as-Saâda>wi>. The Novel tells the story of the life of a woman named Budu>r. She works as a literary critic, but she experienced gender inequalities within the family. This research uses theory of ideological feminist literary criticism to discuss problems in the novel. The research in this thesis aims to find out what forms of gender inequalities experienced by female characters in the novel Zi>nah. Gender inequalities experienced by female charater seen based on the role and position in the public and domestic spheres. The results of this research show that in public sphere, the women do not experience gender inequalities. However, in the domestic sphere, they experience gender inequalities, such as domestic violence, subordination, do not have the right to argue, and stereotype.